Evaluation of Slope Stability Based on Fuzzy Mathematics with Combination Weighting Method of Game Theory - ZHOU Jintao (Renmin Zhujiang)
In order to accurately evaluate the stability of the slope and reduce the risk of landslides,taking the Jiangjiatang slope project in Xingshan,Hubei as an example,this paper selects four first-level indexes namely topography and geomorphology,geological structure,rock and soil properties,and occurrence environment and 16 second-level indexes including slope height,joint development,internal friction angle,and atmospheric rainfall to establish a fuzzy comprehensive evaluation model,weights the slope stability evaluation index system by the combination weighting method of game theory based on the analytic hierarchy process and entropy weight method,and obtains the final weight value of the evaluation index by solving the model.The results show that the index weights obtained by the combination weighting method of game theory are between those calculated by the subjective and objective weighting methods,and the evaluation results of slope stability are consistent with the actual situation,which prove that this method is reasonable.